Técnicas multisensoriales y relaciones lógico matemáticas en niños de preparatoria de la Escuela de Educación Básica Dra. Matilde Hidalgo de Procel de la ciudad de Loja, periodo 2023-2024 - Zambrano Castillo, Ariana Maylee (2024)
Logical-mathematical relationships are a process that allows the acquisition of mathematical concepts such as counting, numbers, correspondence, and serialization; crucial for cognitive development that benefits the maturation of critical logical thinking and the ability to solve events that occur in daily life. The present research aimed to determine how multisensory techniques contribute to strengthening logical-mathematical relationships in preschool children at the Dr. Matilde Hidalgo de Procel Basic Education School in the city of Loja, during the period 2023-2024. Regarding the methodology, it had a quasi-experimental design, with a mixed approach, and the scope was descriptive. Additionally, inductive-deductive and analytical-synthetic methods were addressed. For data collection, the observation technique was applied, and the EVAMAT-0 Test was used as the instrument, which was used to evaluate the level of mathematical competencies in children aged five to six years. The initial results determined that 84% of the sample was in the low zone, while 16% was in the middle zone, demonstrating limited knowledge of the components of geometry, quantity counting, and problem-solving. To reduce these results, a guide of activities based on the use of multisensory techniques was designed and applied. After applying a final evaluation, considerable efficacy was evidenced in the percentage of the low zone, which reduced to 0%, increasing values by 21% in the middle zone and 79% in the high zone. It is concluded that multisensory techniques allow for strengthening the learning of mathematical concepts, as they stimulate the senses directly through games and activities, based on manipulation, and exploration of materials, fragrances, textures, foods, or objects; to achieve the development of logical-mathematical abilities. Key word: human senses, manipulation, mathematical logic, sensory integration, skills, exploration,